China’s Investment in African Special Economic Zones : Prospects, Challenges, and Opportunities - Brautigam, Deborah (World Bank, Washington, DC, 2012)
China's recent moves to establish special economic zones (SEZs) in several African countries can make a significant contribution to industrialization in Africa. But the success of these projects is by no means guaranteed. Meeting the objectives of both China and African countries will require an active partnership and a framework for collaboration that includes engagement from host governments, processes for phasing-in local control, communication and enforcement of standards, and support for integration with local economies.